Władza despotyczna czy demokracja? Partie i wyborcy wobec demokracji w „rządów silnej ręki” - Tomczak, Łukasz (Political Preferences, 2014)
The article concerns the attitudes of parties and their voters towards democracy and support for a "strong-arm government". The research included the five largest Polish civil parties Platforma Obywatelska RP (Civic Platform RP), Prawo I Sprawiedliwość (Law and Justice), Sojusz Lewicy Demokratycznej (Democratic Left Alliance), Twój Ruch (Your Movement), and Polskie Stronnictwo Ludowe (Polish People's Party).The results confirmed that, on the one hand, voters acknowledge democracy as the best political system for Poland; however, on the other hand, a substantial part of them longs for strong authorities. Supporting democracy, they advocate a "strong-arm government". Among left-wing voters, there is three times more proponents of such governments than persons acknowledging another political system as better than democratic one. In the case of political scene centre voters, the number of "strong-arm government" proponents amounts to over four times the number of democracy critics. Nearly half of the right-wing voters supported the "strong-arm government", and every fifth of them did not acknowledge democracy as the best political system.Proponents of democracy dominate in electorates of all parties. Groups in which their advantage over opponents is clearly the smallest include: PiS-voters, persons who declared the will to vote for another formation, and persons who did not want to participate in the elections. Among the PiS-voters, nearly three times more supported "strong-arm government" than opposed it. Among the voters of PO, SLD, and Your Movement, there were more opponents of a "strong-arm government" than its proponents.One may assume that a formation critical towards democracy and favorable towards reinforcement of authority of a strong, charismatic leader could gain among the right-wing voters. It may partially explain why did the KongresNowejPrawicy (Congress of the New Right) receive substantial support in the elections to the European Parliament. KNP criticizes the modern democracy and its leader favorably talked about activities of politicians who apply the methods of a "strong-arm government". On the left side of the political scene there are no premises for the emergence of a political force based on similar views and having greater support.